Mutual Dependence between Sustainable Energy- and Sustainable Agriculture Policies-from the Global and European Perspective; Wzajemna zalezṅosćḿiedzy politykami wspierania zroẃnowazȯnej energii i zroẃnowazȯnego rolnictwa z punktu widzenia perspektywy globalnej i europejskiej - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2012)
The aim of the paper is to present the interrelationship between the sustainable energy, especially renewable energy sector and sustainable agriculture policy from both: the European and the global perspectives. In the world and European economy the role of Renewable Energy Technologies is still increasing. Energy efficiency; sustainable agriculture; renewable energies for rural development belong to main poles of sustainable development in the world economy and its regions. Agriculture is one of the economic sectors to which the EU commitment to reduce emissions of greenhouse gases applies. Like any other economic sector, agriculture produces greenhouse gases and is a major source of the non- CO2 greenhouse gases methane and nitrous oxide. It is also the strong relationship between the sustainable agriculture sector and the renewable energy development possibilities. The sustainable agriculture can be seen as a source of renewable energy. – – Celem artykułu jest zaprezentowanie z perspektywy globalnej i europejskiej zwiazkoẃ miedzy sektorem zroẃnowazȯnej gospodarki energetycznej, w tym w szczegoĺnosći sektorem energii odnawialnej a sektorem rozwoju zroẃnowazȯnego rolnictwa. W gospodarce sẃiatowej i europejskiej zaznacza sie w ostatnich latach systematyczny wzrost znaczenia technologii na rzecz rozwoju energetyki odnawialnej. Głoẃnymi dziedzinami zroẃnowazȯnego rozwoju gospodarki sẃiatowej i jej regionoẃ beda w nadchodzacych latach beda te obszary, ktoŕe bazuja na poprawie efektywnosći energetycznej, zroẃnowazȯnym rolnictwie, odnawialnych energiach ukierunkowanych na rozwoj́ obszaroẃ wiejskich. Rolnictwo jest jednym z wiodacych obszaroẃ, do ktoŕych odnosza sie ustalenia UE dotyczace redukcji emisji gazoẃ cieplarnianych do atmosfery. Podobnie jak i inne sektory gospodarki, rolnictwo jest zŕod́łem emisji nie tylko gazoẃ cieplarnianych ale jest i emitentem innych gazoẃ takich jak metan oraz podtlenek azotu. Istnieje tezṡilna zalezṅosćḿiedzy zroẃnowazȯnym rozwojem rolnictwa i mozl̇iwosćiami pozyskiwania energii ze zŕod́eł odnawialnych, poniewazżroẃnowazȯne rolnictwo wydaje sie bycŕoẃniezi̇stotnym zŕod́łem energii odnawialnej.
Keywords: 330